Evolution of COVID-19 in the Karisimbi Health Zone City of Goma, DRC 2020 - Fidèle Djamba Okitokonda; André André Kalabela Misombo; Ernest Ombha Loshima; Guy Bilulu Suama; Union Sacrée Mwanza Tsonga; Freddy Kambale Kavoga; Éric Panzi Kalunda (Journal of Interventional Epidemiology and Public Health)
Introduction: The Karisimbi health zone reported its first case of Covid-19 in the twentieth epidemiological week of 2020, and up to the thirty-third epidemiological week, it had reported 223 confirmed cases and 22 deaths. There was widespread fear of Covid-19 among the population and healthcare providers. The Karisimbi health zone implemented a number of strategies to combat the pandemic, including epidemiological surveillance of Covid-19, follow-up of contact cases, isolation of confirmed cases and medical management. Nevertheless, the health zone was not analyzing Covid-19-related data on a regular basis, and was not communicating sufficiently on its evolution due to the non-payment of service providers. This justified the present study, the aim of which was to analyze Covid-19-related data and inform decision-makers and health providers about its evolution in order to contribute to the improvement of Covid-19 control strategies. Methods: This cross-sectional descriptive study that used secondary data was carried out in the Karisimbi health zone from the 20th to the 33rd epidemiological week of the year 2020 with a sample of 109 Covid-19 patient files. Descriptive analyses were carried out (proportion and mean) for the study variables derived from Covid-19 patient records. Results: Of the 109 patient files examined, 40.4% (45/109) were asymptomatic for Covid-19, while 59.6% (56/109) were symptomatic. The average turnaround time for results from the Institut National de Recherche Biomédicale was 7 days. The average age of patients with confirmed Covid-19 was 38, and the overall case-fatality rate was 10%. Only 61.5% of cases were followed up in Covid-19 treatment centers, and diabetes mellitus was the only comorbidity encountered, with a diabetes-specific mortality of 100%. From the twentieth epidemiological week to the thirty-third week of 2020, Covid-19 evolved in a fluctuating manner, with a peak in week 28 and numerous deaths in week. Conclusion: From the twentieth epidemiological week to the thirty-third week of the year 2020, Covid-19 evolved in a fluctuating manner, with a peak in week 28 and numerous deaths in week 31. Thus, the delay in reporting laboratory results (7 days turnaround time) did not enable the surveillance team to halt the spread of the disease at an early stage.